Hubungan self-efficacy dengan kemampuan berpikir kritis siswa kelas V dalam mata pelajaran IPAS di MIM Al Akbar Boyolali - Khansa Fariha Salsabila; Dwi Purbowati (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Critical thinking ability is one of the 21st-century skills that need to be developed in elementary school students, especially in science learning. However, students' critical thinking skills are still considered low. One of the factors suspected to influence this is self-efficacy. This study aims to determine the level of self-efficacy, the level of critical thinking ability, and the relationship between self-efficacy and critical thinking ability of fifth-grade students in science subjects at MIM Al Akbar Pandeyan Ngemplak Boyolali in the 2025/2026 academic year. This study uses a quantitative approach with a correlational research type. The research population consisted of 81 fifth-grade students with a sample of 68 students selected using proportionate stratified random sampling techniques. Data were collected through a self-efficacy questionnaire and an essay test of critical thinking skills that met valid and reliable criteria. Data analysis was carried out using descriptive analysis and product-moment correlation through IBM SPSS version 25. The results of the study show that the students' levels of self-efficacy and critical thinking skills are in the moderate category, with percentages of 73.52% and 63.23%, respectively. There is a positive relationship between self-efficacy and critical thinking skills (sig. = 0.001 < 0.05; r = 0.388) with a low-level relationship category.